1994
DOI: 10.1037/0022-0663.86.2.235
|View full text |Cite
|
Sign up to set email alerts
|

Accelerating language development through picture book reading: Replication and extension to a videotape training format.

Abstract: et al. (1988) taught mothers specific interactive techniques to use when reading picture books with their preschool-age children. This intervention program, called dialogic reading, produced substantial effects on preschool children's language development. However, the costs of one-on-one training limit the widespread use of dialogic reading techniques. In this study the authors aimed to replicate and extend the results of the original study of dialogic reading by developing and evaluating an inexpensive vide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
256
1
37

Year Published

1998
1998
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 379 publications
(303 citation statements)
references
References 34 publications
(47 reference statements)
9
256
1
37
Order By: Relevance
“…This agrees with the study of Arnold [1994] that children with the most educated parents (who had degree-level or above qualifications) were on average about 12-13 months ahead of those with the least educated parents (who had no qualifications).…”
Section: Volume 48supporting
confidence: 80%
“…This agrees with the study of Arnold [1994] that children with the most educated parents (who had degree-level or above qualifications) were on average about 12-13 months ahead of those with the least educated parents (who had no qualifications).…”
Section: Volume 48supporting
confidence: 80%
“…Arnold, et al (1994) found that using a videotape to teach the dialogic reading method worked effectively to increase parents' use of dialogic reading skills. However, the generalizability of this finding is greatly limited because all of the children in the study had average or above average expressive and receptive language skills and came from middle or upper Socio-Economic Status (SES) families.…”
Section: Parnters Trainingmentioning
confidence: 99%
“…Si bien numerosos estudios han puesto de manifiesto el efecto positivo de la lectura repetida (BORZONE, 2005) e incluso de la lectura dialógica (SWINSON, ELLIS, 1988;CRAIN-THORESON, DALE, 1992;DEBARYSHE, 1993;ARNOLD et al, 1994;WASIK, BOND, 2001) en las habilidades narrativas de los niños, en estos trabajos no se ha identificado cuál de las tareas llevadas a cabo durante la reconstrucción del cuento y en qué circunstancias podrían dar cuenta de ese efecto positivo. El presente artículo busca identificar precisamente cuáles son las condiciones en las que la reconstrucción de un cuento puede resultar un contexto favorecedor para el desarrollo de las habilidades narrativas en salas de jardín de infantes, describiendo las operaciones cognitivas y discursivas que promueve cada tipo diferente de reconstrucción de cuentos.…”
Section: El Rol Del Adulto: Cómo Apoyar El Procesounclassified